RESPON SISWA TERHADAP PEMBELAJARAN BERKELOMPOK PADA PEMBELAJARAN JARAK JAUH ONLINE - Ramadhan, Syahrul; Atmazaki, Atmazaki; Indriyani, Vivi; Sukma, Elfia (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The COVID-19 pandemic has resulted in learning having turned into online distance learning. The learning is dominated by independent learning, even though the ability to socialize and work in teams is needed at this time. Collaborating is one of the skills needed in the 21st century. Students' opinions differ, because the rapid development of education or internet access does not guarantee the quality of education and student satisfaction. Based on this explanation, the purpose of this study was to determine student responses regarding group learning in online distance learning. This research is a descriptive research using survey method. The instrument used is a questionnaire sheet. The number of respondents who filled out the questionnaire was 484 students. Questionnaire data were analyzed by describing the findings obtained which were described through descriptive statistics. The results showed that students gave a positive response to implementing group learning during online distance learning, for the following reasons: the task was carried out more easily; can get help when experiencing difficulties; can discuss by expressing opinions; can share ideas with group members, etc. However, there are also some weaknesses in this learning, such as the role of group members; domination that works unevenly; talk a lot, etc.